Kajian Literature: Implementasi Perpustakaan Digital di Perguruan Tnggi - Devi, Katrin Setio (UIN Raden Intan Lampung, 2021)
This study aims to describe the implementation of digital libraries in universities. This research is a descriptive study with a literature review method. Five articles were selected that discussed the differences and similarities in user satisfaction between undergraduate and postgraduate students regarding the existence of digital libraries. This study discusses similarities, dissimilarities, provides views, compares and summarizes selected articles. It was found that there are differences and similarities in user perceptions in the use of higher education digital libraries, factors that influence user satisfaction with digital libraries such as system quality, information, and services, digital library affinity, perceived ease and satisfaction felt by users. The five selected articles stated that in a group of academics in which there were undergraduate and postgraduate students had different perceptions of digital libraries. Undergraduate students tend to emphasize speed of access, while postgraduate students prioritize the validity and up-to-date of an information source to meet their needs for information. The results of this study are expected to be a material consideration for policy makers in planning the development of digital libraries so that they are right on target so that their utilization can be maximized